The Denial of Citizenship: “Barbaric” Buenos Aires and the Middle-Class Imaginary - Guano, Emanuela (2004)
This paper explores how, in the Buenos Aires of neoliberalism, middle-class residents strove to make sense of their own impoverishment and their disenfranchisement by generating a consensus on how this city’s modernity was being eroded by the presence of a large mestizo lower class. Through an analysis of the discourse that constructed the urban poor as “barbaric” (i.e., dangerous, polluting, and foreign), I suggest that this representation not only sought to reinforce the fading social difference between the middle- and the lower class, but it also contributed to denying the latter its citizenship in a Buenos Aires that struggled to be “modern”